Electrode plate and preparation method thereof, electrochemical device and electric equipment
By adopting a two-layer electrode material layer structure in the lithium battery electrode sheet, the large and small particle areas are arranged alternately, and large particle areas are contained in the particle column, the energy density and kinetic problems caused by the nanoification of active particles in the lithium battery are solved, and the effect of efficient electrochemical reactions and energy density is achieved.
Patent Information
- Application Number
- CN202411046782.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-31
AI Technical Summary
Although nano-narcopy of active particles in lithium batteries can improve the low-temperature kinetics, it leads to a decrease in the compaction density of the electrode sheet, thereby reducing the volume energy density, making it difficult to take into account both energy density and kinetics.
A two-layer electrode material layer structure is adopted, and each electrode material layer alternately arranges large particle areas and small particle areas along the length direction of the current collector, and contains large particle areas in the particle column to improve the mass transfer ability of the stacked structure and reduce internal resistance.
By controlling the accumulation position of large and small particles, the dynamic performance of the electrode is improved, while taking into account the energy density, which overall improves the performance of the electrode sheet.
Smart Images

Figure BDA0004977497620000171 
Figure HDA0004977497770000011 
Figure HDA0004977497770000012
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrode sheet and a preparation method thereof, an electrochemical device and an electrical equipment. Background Art
[0002] Lithium batteries occupy an important position in the modern energy field due to their performance advantages such as high energy density, low self-discharge rate, good cycle performance and environmental friendliness. They are widely used in electric vehicles, portable appliances and other energy storage devices.
[0003] Nano-sizing active particles in lithium batteries is a common method to shorten the solid phase diffusion distance, increase the specific surface area of electrochemical reaction activity, and improve the low-temperature dynamics of the battery. However, when the particle size is reduced, the compaction density of the electrode is reduced, resulting in a decrease in volume energy density. Therefore, how to balance energy density and dynamics is one of the problems that need to be solved urgently. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose an electrode sheet and a preparation method thereof, an electrochemical device and an electrical equipment, wherein the electrode sheet of the present application has a strong mass transfer capacity, a low internal resistance, good kinetics and energy density, and excellent overall performance.
[0005] The first aspect of the present application provides an electrode sheet, the electrode sheet comprising:
[0006] current collector;
[0007] A first electrode material layer, disposed on at least one side of the current collector;
[0008] A second electrode material layer is disposed on a side of the first electrode material layer away from the current collector;
[0009] Wherein, the first electrode material layer comprises a plurality of first particle regions, the plurality of first particle regions comprise at least one first active material particle region and at least one second active material particle region, the first active material particle regions and the second active material particle regions are alternately arranged along the length direction of the current collector, the first active material particle regions contain first active material particles, the second active material particle regions contain second active material particles, and the average particle size of the first active material particles is greater than the average particle size of the second active material particles;
[0010] The second electrode material layer comprises a plurality of second particle regions, the second particle regions comprise at least one third active material particle region and at least one fourth active material particle region, the third active material particle regions and the fourth active material particle regions are alternately arranged along the length direction of the current collector, the third active material particle regions contain third active material particles, the fourth active material particle regions contain fourth active material particles, and the average particle size of the third active material particles is greater than the average particle size of the fourth active material particles;
[0011] The electrode sheet includes at least one particle column arranged along the length direction of the current collector, and the particle column includes at least one of the first active material particle region and the second active material particle region on the first electrode material layer and at least one of the third active material particle region and the fourth active material particle region on the second electrode material layer;
[0012] Each of the particle columns contains the first active material particle region and / or the third active material particle region.
[0013] According to the electrode sheet of the present application, based on the characteristics of the electrode sheet and the main problems that exist, the present application adopts two layers of electrode material layers along the thickness direction of the current collector, and in each layer of electrode material layer, large particle areas and small particle areas are alternately arranged along the length direction of the current collector, and in the particle columns arranged along the thickness direction of the current collector, each particle column contains a large particle area. Therefore, by controlling the stacking position of large particles and small particles, their respective advantages are brought into play, the mass transfer capacity of the stacking structure is improved, the internal resistance is low, thereby improving the electrode kinetics, while taking into account the energy density, and improving the performance of the electrode sheet as a whole.
[0014] According to the embodiments of the present application, the electrode sheet may also have the following additional technical features:
[0015] According to an embodiment of the present application, the particle column includes the first active material particle region or the second active material particle region on the first electrode material layer and the third active material particle region or the fourth active material particle region on the second electrode material layer.
[0016] According to an embodiment of the present application, the particle column contains the first active material particle region and the fourth active material particle region; or, the particle column contains the second active material particle region and the third active material particle region;
[0017] And / or, the average particle size of the third active material particles is greater than the average particle size of the second active material particles.
[0018] According to an embodiment of the present application, the ratio of the average particle size of the first active material particles to the average particle size of the second active material particles is (1.1-4):1;
[0019] and / or, the ratio of the average particle size of the third active material particles to the average particle size of the fourth active material particles is (1.1-4):1;
[0020] and / or, the ratio of the average particle sizes of the first active material particles to the fourth active material particles is (1.1-4):1;
[0021] and / or, the ratio of the average particle size of the third active material particles to the average particle size of the second active material particles is (1.1-4):1;
[0022] and / or, the average particle sizes of the first active material particles and the third active material particles are independently 0.2 μm to 3.2 μm;
[0023] And / or, the average particle diameters of the second active material particles and the fourth active material particles are independently 0.05 μm to 0.8 μm.
[0024] According to an embodiment of the present application, the ratio of the average particle size of the first active material particles to the average particle size of the second active material particles is (2.2-2.6):1;
[0025] And / or, the ratio of the average particle diameters of the third active material particles to the average particle diameters of the fourth active material particles is (2.2-2.6):1.
[0026] and / or, the average particle sizes of the first active material particles and the third active material particles are independently 0.4 μm to 0.8 μm;
[0027] And / or, the average particle diameters of the second active material particles and the fourth active material particles are independently 0.15 μm to 0.4 μm.
[0028] According to an embodiment of the present application, the number of the second active material particles accounts for 1% to 60% of the total number of the first active material particles and the second active material particles in the first electrode material layer;
[0029] And / or, the number of the fourth active material particles accounts for 1% to 60% of the total number of the third active material particles and the fourth active material particles in the second electrode material layer.
[0030] According to an embodiment of the present application, along the length direction of the current collector, the width of the second active material particle region is greater than the width of the fourth active material particle region;
[0031] and / or, along the length direction of the current collector, the widths of the first active material particle region and the third active material particle region are each independently 10 μm to 100 μm;
[0032] And / or, along the length direction of the current collector, the widths of the second active material particle region and the fourth active material particle region are each independently 1 μm to 20 μm.
[0033] According to an embodiment of the present application, the maximum powder compaction density of the first active material particles and the third active material particles is independently 2.4 g / cm 3 ~2.8g / cm 3 ;
[0034] and / or the maximum powder compaction density of the second active material particles and the fourth active material particles is independently 2.1 g / cm 3 ~2.5g / cm 3 ;
[0035] And / or, the compaction density of the electrode sheet is 2.5 g / cm 3 ~2.7g / cm 3 .
[0036] According to an embodiment of the present application, the first active material particles, the second active material particles, the third active material particles and the fourth active material particles are selected from positive electrode active materials, and the positive electrode active materials include one or more of lithium transition metal oxides, lithium-containing phosphates, sodium transition metal oxides and sodium-containing phosphates;
[0037] Alternatively, the first active material particles, the second active material particles, the third active material particles and the fourth active material particles are selected from one or more of lithium iron phosphate, nickel cobalt lithium manganese oxide ternary material, nickel cobalt aluminum oxide ternary material, lithium manganese oxide and lithium cobalt oxide.
[0038] According to an embodiment of the present application, the first active material particles, the second active material particles, the third active material particles and the fourth active material particles are selected from negative electrode active materials, and the negative electrode active materials include one or more of graphite, silicon and lithium titanate.
[0039] According to an embodiment of the present application, the thickness of the first electrode material layer and the second electrode material layer are each independently 80 μm to 120 μm.
[0040] The second aspect of the present application provides a method for preparing an electrode sheet, the method comprising:
[0041] On at least one side of a current collector, alternately applying a first slurry and a second slurry along a length direction of the current collector to form a first electrode material layer including at least one region of the first active material particles and at least one region of the second active material particles, wherein the first slurry contains first active material particles and the second slurry contains second active material particles;
[0042] On the side of the first electrode material layer away from the current collector, the third slurry and the fourth slurry are alternately applied along the length direction of the current collector to form a second electrode material layer including at least one third active material particle area and at least one fourth active material particle area, the third slurry contains third active material particles, and the fourth slurry contains fourth active material particles.
[0043] The third aspect of the present application provides an electrochemical device, which includes the electrode sheet described in the first aspect of the present application.
[0044] The fourth aspect of the present application provides an electrical equipment, which includes the electrochemical device described in the third aspect of the present application.
[0045] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0047] Figure 1 A schematic diagram of the electrode sheet structure of an embodiment of the present application is shown;
[0048] Figure 2 A schematic diagram of the electrode sheet structure of another embodiment of the present application is shown;
[0049] Figure 3 A schematic diagram of the electrode sheet structure of another embodiment of the present application is shown;
[0050] Figure 4 A schematic diagram of the process of preparing an electrode sheet according to an embodiment of the present application is shown;
[0051] Figure 5 A schematic diagram of the container structure for applying slurry according to an embodiment of the present application is shown.
[0052] Reference numerals:
[0053] 1000 electrode sheet; 100 current collector; 200 first electrode material layer; 300 second electrode material layer; 210 first active material particle area; 220 second active material particle area; 310 third active material particle area; 320 fourth active material particle area; 10 first active material particles; 20 second active material particles; 30 third active material particles; 40 fourth active material particles. DETAILED DESCRIPTION
[0054] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0055] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.
[0056] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0057] In this document, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0058] Nano-sizing active particles in lithium batteries is a common method to shorten the solid phase diffusion distance, increase the specific surface area of electrochemical reaction activity, and improve the low-temperature dynamics of batteries. However, when the particle size is reduced, the compaction density of the electrode is reduced, resulting in a decrease in volume energy density.
[0059] At present, the existing technology widely adopts the method of matching large and small particles to take into account energy density and dynamics. However, on the one hand, the higher the utilization rate of the stacking space of large and small particles, the lower the porosity of the pole piece, resulting in a decrease in the liquid phase mass transfer capacity; on the other hand, the increase in the doping amount of small particles increases the number of particles per unit volume, resulting in an increase in the number of charge transfer interfaces. In other words, when the proportion of small particles exceeds a certain value, the electron and ion transmission capabilities of the pole piece deteriorate, resulting in an increase in the internal resistance of the battery as the doping amount of small particles increases. Ultimately, the battery doped with small particles presents a contradiction in that the low-temperature continuous charge and discharge capability is improved but the pulse charge and discharge capability (especially at room temperature) is reduced.
[0060] The existing grading design of using small particles coated with carbon + large particles not coated with carbon is expected to provide an electron transmission path for the small particles coated with carbon, and the large particles not coated with carbon provide an ion transmission path, so as to achieve the purpose of rapid transmission of both electrons and ions at the interface. However, since the ionic conductivity of the active material is worse than that of the electrolyte, the electronic conductivity is much worse than that of conductive agents such as carbon black / acetylene black. Therefore, the electrochemical reaction of the large particles not coated with carbon in the above technology can only start from a single point of contact with the conductive agent, and cannot start the reaction from all directions on the surface like the carbon-coated active particles, resulting in a significant decrease in the proportion of lithium that can be inserted and removed from the large particles at a large rate and low temperature with kinetic constraints, thereby affecting the overall battery performance. Therefore, this method of improving the ion transmission capacity of the electrode by sacrificing the ability of large particles to conduct electrons is not a good strategy.
[0061] Based on the characteristics of the electrode sheet and the main problems that exist, this application adopts two layers of electrode material along the thickness direction of the current collector. In each layer of electrode material, large particle areas and small particle areas are arranged alternately along the length direction of the current collector. In the particle columns arranged along the thickness direction of the current collector, each particle column contains a large particle area. Therefore, by controlling the stacking position of large particles and small particles, their respective advantages are brought into play, the mass transfer capacity of the stacking structure is improved, the internal resistance is reduced, and the electrode kinetics are improved. No new materials are introduced, and the compaction density of the electrode sheet is not changed. The energy density is taken into account, and the overall performance can be improved.
[0062] In the terminology of this application, "mass transfer" refers to the migration process of charges / ions from the electrolyte phase to the electrode active material phase inside the battery. This process is crucial to the charge and discharge performance of the battery and directly determines the battery's charge and discharge rate, energy density, cycle life and other performance. The mass transfer process mainly includes two aspects: the diffusion of charges / ions in the liquid phase to the electrode surface and the diffusion of charges / ions in the solid phase inside the electrode material.
[0063] Based on this, in the first aspect of the present application, an electrode sheet is proposed. Figure 1 A schematic diagram of the electrode sheet structure of the present application is shown, where the electrode sheet 1000 includes: a current collector 100, a first electrode material layer 200 and a second electrode material layer 300, wherein the first electrode material layer 200 is disposed on at least one side of the current collector 100, and the second electrode material layer 300 is disposed on a side of the first electrode material layer 200 away from the current collector 100.
[0064] Specifically, the first electrode material layer 200 includes a plurality of first particle regions, the plurality of first particle regions include at least one first active material particle region 210 and at least one second active material particle region 220, the first active material particle regions 210 and the second active material particle regions 220 are alternately arranged along the length direction of the current collector 100, the first active material particle regions 210 contain first active material particles 10, the second active material particle regions 220 contain second active material particles 20, and the average particle size of the first active material particles 10 is greater than the average particle size of the second active material particles 20;
[0065] The second electrode material layer 300 includes a plurality of second particle regions, the second particle regions include at least one third active material particle region 310 and at least one fourth active material particle region 320, the third active material particle regions 310 and the fourth active material particle regions 320 are alternately arranged along the length direction of the current collector 100, the third active material particle regions 310 contain third active material particles 30, the fourth active material particle regions 320 contain fourth active material particles 40, and the average particle size of the third active material particles 30 is greater than the average particle size of the fourth active material particles 40;
[0066] The electrode sheet 10 includes at least one particle column arranged along the length direction of the current collector 100, and the particle column includes at least one of the first active material particle region 210 and the second active material particle region 220 on the first electrode material layer 200 and at least one of the third active material particle region 310 and the fourth active material particle region 320 on the second electrode material layer 300;
[0067] Each particle column contains a first active material particle region 210 and / or a third active material particle region 230 .
[0068] For ease of understanding, in this application, the first active material particles 10 and the third active material particles 30 are also referred to as "large particles", and the corresponding particle areas are also referred to as "large particle areas"; the second active material particles 20 and the fourth active material particles 40 are also referred to as "small particles", and the corresponding particle areas are also referred to as "small particle areas". The materials and sizes of the large particles are the same or different, and the materials and sizes of the small particles are the same or different, which can be flexibly selected according to actual needs. The length direction of the current collector is also referred to as the "transverse direction", and the thickness direction of the current collector is also referred to as the "longitudinal direction".
[0069] There are three types of pore structures formed by the accumulation of large and small particles: the first type is the pore structure formed by the accumulation of large particles, which has the best mass transfer capacity; the second type is the pore structure formed by the accumulation of small particles, which has a poor mass transfer capacity; the third type is the pore structure formed by the accumulation of large particles and small particles, which has a lower mass transfer capacity than the first type. Therefore, if the electrode with mixed accumulation of large and small particles can transfer mass through the first pore structure, the kinetics will be optimal.
[0070] Based on this, in the electrode sheet of the present application, large particles and small particles are partitioned in the horizontal and vertical directions to make their respective advantages play to each other. Specifically, large particle areas and small particle areas are arranged alternately in the horizontal direction, at least two layers of structure are adopted in the vertical direction, and the two-layer structure of each longitudinal particle column contains a large particle area. Large particles are piled up to form a longitudinal channel from the current collector to the diaphragm side, which serves as the main road for the longitudinal transmission of charges / ions and completes the task of longitudinal mass transfer. The interval formed by the accumulation of small particles and small particles serves as a lateral branch line to obtain electrons and ions required for electrochemical reactions from the main road. In this way, the problems of pore blockage and increased electrochemical mass transfer tortuosity caused by the doping of small particles in conventional mixed stacking structures can be avoided, so that the doped small particles only play their kinetic advantages of shortening the solid-phase diffusion distance and increasing the specific surface area of electrochemical reaction activity.
[0071] The following will be combined Figure 2 The advantages of the electrode sheet structure design of this application are elaborated in detail:
[0072] The lithium ions released by small particle A need to be transferred to the diaphragm side and then to the counter electrode, and the electrons released by small particle B need to be transferred to the current collector and then to the external circuit. Through the longitudinal channel mass transfer formed by the large particle stacking interval, the lithium ions released by A need to cross 4 large particles to reach the diaphragm side (the transmission distance is recorded as a1), and the electrons released by B also need to cross 4 large particles to reach the current collector (the transmission distance is recorded as b1). This is the shortest distance that particles A and B need to cross for mass transfer. Conversely, if the mass transfer occurs in the small particle accumulation area, the lithium ions released by A need to cross 7 small particles to reach the diaphragm side (the transmission distance is recorded as a2), and the electrons released by B also need to cross 7 small particles to reach the current collector side (the transmission distance is recorded as b2). Therefore, by using the longitudinal channel mass transfer formed by the large particle stacking interval, the number of particles crossed by lithium ions is small and the mass transfer distance is short, thereby improving the mass transfer capacity and the kinetic benefits are more significant.
[0073] It can be understood that the electrode sheet 1000 of the present application includes at least one first electrode material layer 100 and at least one second electrode material layer 200, and the first electrode material layer 100 and the second electrode material layer 200 are alternately stacked in sequence.
[0074] For example, each particle column may contain both large particles and small particles, for example Figure 1 The first column on the left can also contain large particles, such as Figure 3 In the first column on the right side, it is sufficient to ensure that small particles are not contained at the same time. It is preferred to contain both large particles and small particles, which helps to further reduce the internal resistance and improve the mass transfer capacity.
[0075] In some embodiments of the present application, the particle array includes the first active material particle area 210 or the second active material particle area 220 on the first electrode material layer 200 and the third active material particle area 310 or the fourth active material particle area 320 on the second electrode material layer 300. Figure 1 For example, the first column of particles on the left side of the first electrode material layer 200 contains only large particles, which is more conducive to mass transfer, reducing internal resistance, and improving battery kinetic performance compared to containing both large particles and small particles (stacked up and down) in the column. Similarly, each particle column of the second electrode material layer 300 contains a third active material particle area 310 or a fourth active material particle area 320. As a result, it is more conducive to mass transfer, reducing internal resistance, and improving battery kinetic performance.
[0076] In some embodiments of the present application, the particle column contains a first active material particle region 210 and a fourth active material particle region 320, for example Figure 1 or, the particle column contains a second active material particle region 220 and a third active material particle region 310, for example Figure 1 The first column on the right.
[0077] In some embodiments of the present application, the average particle size of the first active material particles 10 is greater than the average particle size of the fourth active material particles 40. Thus, the situation where all particles in a column are small is avoided.
[0078] In some embodiments of the present application, the thickness of the first electrode material layer 200 and the second electrode material layer 300 are independently 80 μm to 120 μm, for example, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, or a range formed by any two values as endpoint values. Thus, the electrochemical device containing the electrode sheet of the present application has better rate performance and cycle stability.
[0079] In some embodiments of the present application, the compaction density of the electrode sheet 1000 is 2.5 g / cm 3 ~2.7g / cm 3 , for example, it can be 2.5 g / cm 3 , 2.55g / cm 3 , 2.6g / cm 3 , 2.65g / cm 3 , 2.7g / cm 3 The present application improves the mass transfer capacity of the electrode sheet without sacrificing energy density. The above compaction density can further improve the specific capacity and energy density of the electrochemical device, and the charge and discharge efficiency and cycle stability are better.
[0080] In this application, the term "compacted density" refers to the maximum packing density of the electrode material under specific conditions, usually expressed in grams per cubic centimeter (g / cm 3 Specifically, the compaction density measurement method of the present application is as follows: sampling is performed at three random positions of the electrode sheet using a 1.5 mm diameter circular cutter, and the thickness is measured using a micrometer and the weight is weighed using an electronic balance to calculate the compaction density of the electrode sheet.
[0081] In some embodiments of the present application, the maximum powder compaction density of the first active material particles 10 and the third active material particles 30 is independently 2.4 g / cm 3 ~2.8g / cm 3 , for example, it can be 2.4 g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 Or any two values as the range value formed by the endpoint values. In some embodiments of the present application, the maximum powder compaction density of the second active material particles 20 and the fourth active material particles 40 is independently 2.1 g / cm 3 ~2.5g / cm 3 , for example, it can be 2.1 g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 Or any two values as the range value formed by the endpoint values. Therefore, the pore structure formed between large particles and the pore structure formed between small particles are better, and the mass transfer distance is shorter, which is conducive to the longitudinal channel formed by large particles to complete the longitudinal mass transfer, and also conducive to the horizontal branch formed by the accumulation of small particles to obtain electrons and ions, thereby improving the mass transfer capacity as a whole and taking into account the energy density.
[0082] In the present application, the term "maximum powder compaction density" refers to the particle being pressed at a pressure of 200 MPa for 10 seconds, measured according to the method of GB / T 1479.1 2011.
[0083] In some embodiments of the present application, the average particle size of the third active material particles 30 is greater than the average particle size of the second active material particles 20. In other embodiments of the present application, the ratio of the average particle size of the first active material particles 10 to the second active material particles 20, the ratio of the average particle size of the third active material particles 30 to the fourth active material particles 40, and the ratio of the average particle size of the first active material particles 10 to the fourth active material particles 40 is (1.1-4):1, and the ratio of the average particle size of the third active material particles 30 to the second active material particles 20 is (1.1-4):1 is (1.1-4):1, for example, it can be 1.1, 1.5, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.5, 4 or any two values as the range value formed by the endpoint values, preferably (2.2-2.6):1. In some other embodiments of the present application, the average particle size of the third active material particles 30 is greater than the average particle size of the second active material particles 20. In some other embodiments of the present application, the average particle sizes of the first active material particles and the third active material particles are independently 0.2μm to 3.2μm, for example, 0.4μm, 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.4μm, 2.5μm, 2.6μm, 2.8μm, 3μm, 3.2μm or a range value formed by any two values as endpoint values, preferably 0.4μm to 0.8μm. In some other embodiments of the present application, the average particle sizes of the second active material particles and the fourth active material particles are independently 0.05μm to 0.8μm, for example, 0.05μm, 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.6μm, 0.8μm or a range value formed by any two values as endpoint values, preferably 0.15μm to 0.4μm, more preferably 0.15μm to 0.3μm.
[0084] As a result, the pore structure formed between large particles and the pore structure formed between small particles are better, and the mass transfer distance is shorter, which is beneficial for the longitudinal channels formed by large particles to complete the longitudinal mass transfer, and also beneficial for the transverse branches formed by the accumulation of small particles to obtain electrons and ions, thereby improving the overall mass transfer capacity while taking into account the energy density.
[0085] In this application, the average particle size is expressed as D 50 The value indicates that "D 50 The "value" refers to the particle size value in the middle of the distribution after the particles are arranged in order of size, that is, among all the particles, half of the particles have a particle size smaller than D 50 value, the other half of the particles are larger than D50 Value. 50 The determination of the value is usually based on the cumulative frequency curve of the particle size distribution, that is, the cumulative percentage of the particle size. This curve shows the cumulative distribution of particle sizes from small to large. On the cumulative frequency curve, D 50 The value corresponds to the point where the cumulative frequency is 50%. In other words, D 50 The value is the particle size value corresponding to the intersection of the cumulative curve and the 50% cumulative frequency line.
[0086] In some embodiments of the present application, along the length direction of the current collector 100, the width of the second active material particle region is greater than the width of the fourth active material particle region. In some embodiments of the present application, along the length direction of the current collector 100, the widths of the first active material particle region and the third active material particle region are independently 1 μm to 100 μm, for example, 1 μm, 10 μm, 30 μm, 50 μm, 60 μm, 80 μm, 100 μm, or a range value formed by any two values as endpoint values. In some embodiments of the present application, along the length direction of the current collector 100, the widths of the second active material particle region and the fourth active material particle region are independently 1 μm to 20 μm, for example, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, or a range value formed by any two values as endpoint values. As a result, the pore structure formed between large particles and the pore structure formed between small particles are better, and the mass transfer distance is shorter, which is beneficial for the longitudinal channels formed by large particles to complete the longitudinal mass transfer, and also beneficial for the transverse branches formed by the accumulation of small particles to obtain electrons and ions, thereby improving the overall mass transfer capacity while taking into account the energy density.
[0087] In some embodiments of the present application, the number of the second active material particles 20 accounts for 1% to 60% of the total number of the first active material particles 10 and the second active material particles 20 in the first electrode material layer 200 (also referred to as "doping amount" in the present application), for example, it can be 1%, 10%, 20%, 30%, 40%, 50%, 60% or a range value formed by any two values as endpoint values. In other embodiments of the present application, the number of the fourth active material particles 40 accounts for 1% to 60% of the total number of the third active material particles 30 and the fourth active material particles 40 in the second electrode material layer 300, for example, it can be 1%, 10%, 20%, 30%, 40%, 50%, 60% or a range value formed by any two values as endpoint values. As a result, the pore structure formed between large particles and the pore structure formed between small particles are better, and the mass transfer distance is shorter, which is beneficial for the longitudinal channels formed by large particles to complete the longitudinal mass transfer, and also beneficial for the transverse branches formed by the accumulation of small particles to obtain electrons and ions, thereby improving the overall mass transfer capacity while taking into account the energy density.
[0088] In this application, there is a quantitative correspondence between the width of the particle column (also referred to as "lateral partition width" in this application) along the length direction of the current collector and the size of the large and small particles and the doping amount of the small particles. Assume that the average size of the large and small particles is d 1 ,d 2 , the maximum powder compaction density is ρ 1 , 2 (The maximum powder compaction density is the value in the powder pressure-compaction curve of the particle, where the compaction density remains almost unchanged as the pressure increases), the small particle doping amount is x, and the lateral partition widths are w 1 、w 2 (The maximum compacted powder density depends on the size). If w 1 =n 1 d 1 (n 1 is a natural number), then w 2 =n 2 d 2 =n 1 d 1 ρ 1 x / (ρ 2 (1-x))(n 2 >1 and is a natural number), n 2 The ideal solution is 2. If the process can be realized, we hope that n 2 The smaller the better (too many small particles will affect mass transfer). 2 is the control parameter, and n is obtained by the above formula 2 / n 1= d 1 ρ 1 x / (d 2 ρ 2 (1-x)), when the size of large and small particles and the amount of small particle doping are determined, the ratio of the lateral partition width coefficient n 2 / n 1 Sure.
[0089] In some embodiments of the present application, the first active material particles 10, the second active material particles 20, the third active material particles 30 and the fourth active material particles 40 are selected from positive electrode active materials, and the positive electrode active materials include one or more of lithium transition metal oxides, lithium-containing phosphates, sodium transition metal oxides and sodium-containing phosphates.
[0090] In some embodiments of the present application, the first active material particles 10, the second active material particles 20, the third active material particles 30 and the fourth active material particles 40 are selected from one or more of lithium iron phosphate, nickel cobalt lithium manganese oxide ternary material, nickel cobalt aluminum oxide ternary material, lithium manganese oxide and lithium cobalt oxide.
[0091] In some embodiments of the present application, the first active material particles 10 , the second active material particles 20 , the third active material particles 30 and the fourth active material particles 40 are selected from negative electrode active materials, and the negative electrode active materials include one or more of graphite, silicon and lithium titanate.
[0092] In some embodiments of the present application, for the positive electrode sheet, the current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0093] In some embodiments of the present application, for the negative electrode sheet, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0094] In some embodiments of the present application, the first electrode material layer 200 and the second electrode material layer 300 each independently include a binder and a conductive agent. The binder is used to bond and maintain the electrode material layer, enhance the electronic contact between the material layer and the current collector, and better stabilize the structure of the electrode sheet. The conductive agent enables the electrode sheet to have good charge and discharge performance, reduce the contact resistance of the electrode sheet, and accelerate the movement rate of electrons, thereby improving the charge and discharge efficiency of the electrode sheet. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, and the binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0095] The second aspect of the present application provides a method for preparing an electrode sheet, see Figure 3 The method includes: S100 forming a first electrode material layer and S200 forming a second electrode material layer. Each step will be described in detail below.
[0096] S100 Forming a first electrode material layer
[0097] In this step, a first slurry and a second slurry are alternately applied along the length direction of the current collector on at least one side of the current collector to form a first electrode material layer including at least one first active material particle area and at least one second active material particle area, the first slurry containing first active material particles and the second slurry containing second active material particles.
[0098] S200 Forming a second electrode material layer
[0099] In this step, on the side of the first electrode material layer away from the current collector, the third slurry and the fourth slurry are alternately applied along the length direction of the current collector to form a second electrode material layer including at least one third active material particle area and at least one fourth active material particle area, the third slurry contains third active material particles, and the fourth slurry contains fourth active material particles.
[0100] In the present application, there is no strict limitation on the method of applying the slurry, and the electrode material layer can be formed by coating, 3D printing or honeycomb structure. For example, Figure 5 A first device filled with a first layer of slurry for forming a first electrode material layer and a second device filled with a second layer of slurry for forming a second electrode material layer are shown. Each device contains a plurality of partition grooves alternately filled with different active particle slurries. A discharge port is provided at the bottom of each partition groove, and the discharge port is controlled to extrude the slurry in the partition groove. The first electrode material layer can be completely formed and dried before forming the second electrode material layer; or when forming a part of the first electrode material layer, the second layer of filler can be coated on the dried layer, thereby forming the first electrode material layer and the second electrode material layer simultaneously to improve production efficiency. Figure 5 "No material discharge" means that the separation groove is filled with slurry, and the discharge port is not opened during coating; "No material" means that the slurry is not filled, so that the separation grooves filled with large particles and small particles of the first device and the second device are staggered to achieve large particles and small particles in the particle column. "No material discharge" and "material discharge" can be interchanged, and one or two of the two separation grooves can be removed, as long as the surface of the current collector corresponding to the area is not coated with slurry.
[0101] A third aspect of the present application provides an electrochemical device, which includes the electrode sheet according to the first aspect of the present application.
[0102] The electrochemical device of the present application may include any device that generates an electrochemical reaction, and specific examples thereof include but are not limited to primary batteries, secondary batteries, capacitors, etc. Optionally, the electrochemical device may be a lithium-ion secondary battery.
[0103] In some embodiments of the present application, a lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions, lithium ions, are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0104] The present application has no particular restrictions on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected. In some embodiments of the present application, the isolation membrane may be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.
[0105] The present application has no particular restriction on the type of electrolyte. For example, the electrolyte solvent may be two or more of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC); the electrolyte may be lithium hexafluorophosphate / sodium (Li / NaPF 6 ), lithium / sodium perchlorate (Li / NaClO 4 ), one or more of lithium / sodium trifluorosulfonimide (Li / NaFSI).
[0106] The lithium-ion battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells may be assembled into a battery module, and the number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0107] The fourth aspect of the present application provides an electrical device, which includes the electrochemical device described in the third aspect of the present application.
[0108] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0109] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0110] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.
[0111] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0112] It should be noted that the features and advantages described above for the electrode sheet of the first aspect of the present application are also applicable to the method for preparing the electrode sheet of the second aspect of the present application, the electrochemical device of the third aspect and the electrical equipment of the fourth aspect, and will not be repeated here.
[0113] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0114] Example 1
[0115] 1. Preparation of positive electrode sheet
[0116] (1) Provide aluminum foil, large particle LFP (LiFePO 4 ) and small particle LFP (LiFePO 4 ), where the average particle size of large LFP particles is 1 =0.6μm, average particle size of small particle LFP d 2 =0.4μm.
[0117] (2) 95% of large particle LPF, 2% of carbon black and 3% of PVDF were stirred evenly to obtain large particle slurry. In the same way, small particle LPF was prepared to obtain small particle slurry.
[0118] (3) On one side of the aluminum foil, coating is performed by a 3D printer, see Figure 5 In the first layer of filler, the separation grooves are filled with large particle slurry and small particle slurry alternately from the first strip, and the last strip is not filled with slurry. In the second layer of filler, the separation grooves are filled with large particle slurry and small particle slurry alternately from the first strip. Large particle coating width w 1 =80μm, small particle coating width w 2=10μm.
[0119] The first layer of filler is applied first. The first electrode material layer formed has a starting strip of large particles from the left, a material layer thickness of 100 μm, a small particle doping amount of 10%, and a maximum powder compaction density of large particles and small particles of 2.65 g / cm 3 and 2.35g / cm 3 .
[0120] After the first electrode material layer loses its fluidity, the second electrode material layer is printed on the surface of the first electrode material layer. No material is discharged from the first strip from the left. Starting from the second strip, small particle slurry and large particle slurry are alternately filled in sequence, and the position of filling small particle slurry corresponds to the large particle area in the first electrode material layer, and the position of filling large particle slurry corresponds to the small particle area in the first electrode material layer to form the second electrode material layer. The material layer thickness is 100 μm, the small particle doping amount is 10%, and the maximum powder compaction density of large particles and small particles is 2.65 g / cm 3 and 2.35g / cm 3 Note: The maximum powder compaction density is measured by holding the particles at a pressure of 200 MPa for 10 seconds according to the GB / T 1479.1 2011 method.
[0121] Finally, after baking and roll pressing, the positive electrode sheet is obtained.
[0122] 2. Preparation of negative electrode sheet
[0123] Graphite, 2% carbon black and 3% PVDF were mixed evenly to obtain negative electrode slurry. The negative electrode slurry was coated on the surface of copper foil, dried and rolled to obtain the negative electrode.
[0124] 3. Place the positive electrode sheet, negative electrode sheet, separator (Celgard 2300 microporous membrane) and electrolyte (containing 1.0 mol / L LiPF 6 , the solvent is ethylene carbonate (EC): dimethyl carbonate (DMC) with a volume ratio of 1:1) to assemble into a soft-pack battery E1 with a designed battery capacity of 1.8Ah.
[0125] The differences between Examples 2 to 6 and Example 1 are shown in Table 1. By setting one of the large particle coating width W1 and the small particle coating width W2, the average particle size d of the large particle LFP 1 , the average particle size d of small particle LFP 2 and the small particle doping amount x, and the maximum powder compaction density ρ of the large particles is determined 1 and the maximum powder compaction density of small particles ρ 2 , according to w 1 =n 1 d 1 and w2 =n 2 d 2 =n 1 d 1 ρ 1 x / (ρ 2 (1-x)), calculate the other of the large particle coating width W1 and the small particle coating width W2. Specifically,
[0126] The difference between Example 2 and Example 1 is that the average particle size d of the large particles is 1 =0.6μm, average particle size of small particles d 2 =0.4μm, the small particle doping amount is 50%, the small particle coating width W2 is 10μm, and the maximum powder compaction density ρ of the large particles is measured 1 and the maximum powder compaction density of small particles ρ 2 , the large particle coating width W1 is calculated to be 80 μm. A soft pack battery E2 is obtained.
[0127] The difference between Example 3 and Example 1 is that the average particle size d of the large particles is 1 =0.6μm, average particle size of small particles d 2 =0.25μm, the small particle doping amount is 10%, the small particle coating width W2 is 10μm, and the maximum powder compaction density ρ of the large particles is measured 1 and the maximum powder compaction density of small particles ρ 2 , the large particle coating width W1 is calculated to be 10 μm. A soft pack battery E3 is obtained.
[0128] The difference between Example 4 and Example 1 is that the average particle size d of the large particles is 1 =1.6μm, average particle size of small particles d 2 =0.4μm, the small particle doping amount is 10%, the small particle coating width W2 is 10μm, and the maximum powder compaction density ρ of the large particles is measured 1 and the maximum powder compaction density of small particles ρ 2 , the large particle coating width W1 is calculated to be 10 μm. A soft pack battery E4 is obtained.
[0129] The difference between Example 5 and Example 1 is that the average particle size d 1 =0.3μm, average particle size of small particles d 2 =0.25μm, the small particle doping amount is 10%, the small particle coating width W2 is 10μm, and the maximum powder compaction density ρ of the large particles is measured 1 and the maximum powder compaction density of small particles ρ 2 , the large particle coating width W1 is calculated to be 90 μm. A soft pack battery E5 is obtained.
[0130] The difference between Example 6 and Example 1 is that the average particle size d 1 =0.6μm, average particle size of small particles d 2 =0.4μm, the doping amount of small particles is 70%, the coating width W1 of large particles is 10μm, and the maximum powder compaction density ρ of large particles is measured 1 and the maximum powder compaction density of small particles ρ 2 , the small particle coating width W2 is calculated to be 25 μm. A soft pack battery E6 is obtained.
[0131] Comparative Example 1
[0132] The difference between this comparative example and Example 1 is that the preparation steps of the positive electrode sheet are as follows:
[0133] 1. Provide aluminum foil, large particle LFP and small particle LFP, among which the average particle size d of large particle LFP 1 =0.6μm, average particle size of small particle LFP d 2 =0.4μm.
[0134] 2. 95% of LFP particles (the doping amount of small-particle LFP is 10%), 2% of conductive agent carbon black and 3% of PVDF are mixed evenly to obtain active particle slurry.
[0135] 3. On one side of the aluminum foil, the active particle slurry is coated, and after baking and roll pressing, a positive electrode sheet is obtained.
[0136] Comparative Example 2
[0137] The difference between this comparative example and Example 1 is that the preparation steps of the positive electrode sheet are as follows:
[0138] 1. Provide aluminum foil, large particle LFP and small particle LFP, among which the average particle size d of large particle LFP 1 =0.6μm, average particle size of small particle LFP d 2 =0.4μm.
[0139] 2. 95% of LFP particles (the doping amount of small particle LFP is 50%), 2% of conductive agent carbon black and 3% of PVDF are mixed evenly to obtain active particle slurry.
[0140] 3. On one side of the aluminum foil, the active particle slurry is coated, and after baking and roll pressing, a positive electrode sheet is obtained.
[0141] Comparative Example 3
[0142] The difference between this comparative example and Example 1 is that the preparation steps of the positive electrode sheet are as follows:
[0143] 1. Provide aluminum foil, large particle LFP and small particle LFP, among which the average particle size d of large particle LFP1 =0.6μm, average particle size of small particle LFP d 2 =0.25μm.
[0144] 2. 95% of LFP particles (the doping amount of small-particle LFP is 10%), 2% of conductive agent carbon black and 3% of PVDF are mixed evenly to obtain active particle slurry.
[0145] 3. On one side of the aluminum foil, the active particle slurry is coated, and after baking and roll pressing, a positive electrode sheet is obtained.
[0146] Comparative Example 4
[0147] The difference between this comparative example and Example 1 is that in step 1 (3), after the first electrode material layer loses fluidity, the second electrode material layer is printed on the surface of the first electrode material layer, the first strip from the left is empty, and the small particle slurry and the large particle slurry are alternately filled in sequence from the second strip, and the position where the small particle slurry is filled corresponds to the small particle area in the first electrode material layer, and the position where the large particle slurry is filled corresponds to the large particle area in the first electrode material layer, so as to form the second electrode material layer. Thus, the prepared electrode sheet includes two particle columns arranged along the length direction of the current collector, namely, a particle column of all large particles and a particle column of all small particles.
[0148] Test Case
[0149] In this test example, the electrode sheet compaction density of Examples 1 to 6 and Comparative Examples 1 to 4 and the battery DC internal resistance of the battery under different temperature conditions were tested respectively, and the test method was as follows:
[0150] Electrode sheet compaction density: Samples are taken at three random positions of the electrode sheet using a 1.5 mm diameter circular cutter, and the thickness is measured with a micrometer and the weight is weighed with an electronic balance to calculate the compaction density of the electrode sheet.
[0151] The battery was discharged at 1 / 3C constant current to 2.0V at room temperature, and charged at 1 / 3C constant current to 50% SOC. It was discharged at 1.5C constant current for 30s at 25℃ and -10℃ respectively, and the voltage before and after discharge was recorded. The discharge DCIR (mΩ) was calculated as (pre-discharge voltage - post-discharge voltage) / discharge current * 1000.
[0152] The results are shown in Table 1. The overall performance of batteries E1-E6 is better than that of batteries C1-C4. It can be seen from batteries E1 and C1, E2 and C2 that compared with batteries without large and small particles, the battery prepared by the large and small particle stacking method of the present application can improve the mass transfer capacity of the electrode sheet, reduce the internal resistance, and improve the kinetic performance.
[0153] In battery C3, based on large particles d 1 and small particles2 The average particle size satisfies d 1 ×(√2-1)=d 2 , under this ratio, the maximum compaction density can be formed. Although it will make its volume energy density the highest, it will cause a significant reduction in mass transfer performance, which is reflected in the significant increase in the internal resistance of the battery and poor dynamic performance. Compared with battery C3, battery E3 adopts the large and small particle stacking method of the present application. Although the compaction density is slightly reduced, it can greatly improve the mass transfer capacity, greatly reduce the internal resistance of the battery, and significantly improve the dynamic performance.
[0154] Comparing batteries E1 and E2, the reduction in internal resistance of E2 compared to C2 is greater than that of E1 compared to C1, indicating that increasing the doping amount of small particles brings more obvious advantages to this application, the mass transfer capacity of the battery is more significantly improved, the internal resistance is reduced to a greater extent, and the kinetic benefit is higher.
[0155] Compared with batteries E1 and E3, the average particle size ratio of large particles to small particles in battery E3 is slightly higher, which is beneficial to improving the mass transfer capacity, thereby reducing the internal resistance of the battery and increasing the compaction density.
[0156] Compared with batteries E1 and E4, the average particle size of large particles in battery E4 is higher, and the corresponding average particle size ratio of large particles to small particles is higher, which hinders mass transfer and causes the internal resistance of the battery to be higher.
[0157] Compared with batteries E3 and E5, the average particle size of large particles in battery E5 is relatively low, and the corresponding average particle size ratio of large particles to small particles is relatively low, which will also hinder mass transfer and cause the internal resistance of the battery to be relatively high.
[0158] Compared with battery E6 and E1, the amount of small particles doped in battery E6 is too high, which will reduce the mass transfer capacity and cause the internal resistance of the battery to be higher.
[0159] Table 1 DC internal resistance of different batteries under different temperature conditions
[0160]
[0161] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. An electrode sheet, characterized in that: include: current collector; A first electrode material layer, disposed on at least one side of the current collector; A second electrode material layer is disposed on a side of the first electrode material layer away from the current collector; Wherein, the first electrode material layer comprises a plurality of first particle regions, the plurality of first particle regions comprise at least one first active material particle region and at least one second active material particle region, the first active material particle regions and the second active material particle regions are alternately arranged along the length direction of the current collector, the first active material particle regions contain first active material particles, the second active material particle regions contain second active material particles, and the average particle size of the first active material particles is greater than the average particle size of the second active material particles; The second electrode material layer comprises a plurality of second particle regions, the second particle regions comprise at least one third active material particle region and at least one fourth active material particle region, the third active material particle regions and the fourth active material particle regions are alternately arranged along the length direction of the current collector, the third active material particle regions contain third active material particles, the fourth active material particle regions contain fourth active material particles, and the average particle size of the third active material particles is greater than the average particle size of the fourth active material particles; The electrode sheet includes at least one particle column arranged along the length direction of the current collector, and the particle column includes at least one of the first active material particle region and the second active material particle region on the first electrode material layer and at least one of the third active material particle region and the fourth active material particle region on the second electrode material layer; Each of the particle columns contains the first active material particle region and / or the third active material particle region.
2. The electrode sheet according to claim 1, characterized in that: The particle array includes the first active material particle region or the second active material particle region on the first electrode material layer and the third active material particle region or the fourth active material particle region on the second electrode material layer.
3. The electrode sheet according to claim 1 or 2, characterized in that: The particle column contains the first active material particle region and the fourth active material particle region; or the particle column contains the second active material particle region and the third active material particle region; And / or, the average particle size of the third active material particles is greater than the average particle size of the second active material particles.
4. The electrode sheet according to claim 1, characterized in that: The ratio of the average particle size of the first active material particles to the average particle size of the second active material particles is (1.1-4):1; and / or, the ratio of the average particle size of the third active material particles to the average particle size of the fourth active material particles is (1.1-4):1; and / or, the ratio of the average particle sizes of the first active material particles to the fourth active material particles is (1.1-4):1; and / or, the ratio of the average particle size of the third active material particles to the average particle size of the second active material particles is (1.1-4):1; and / or, the average particle sizes of the first active material particles and the third active material particles are independently 0.2 μm to 3.2 μm; And / or, the average particle diameters of the second active material particles and the fourth active material particles are independently 0.05 μm to 0.8 μm.
5. The electrode sheet according to claim 1, characterized in that: The ratio of the average particle size of the first active material particles to the average particle size of the second active material particles is (2.2-2.6):1; and / or, the ratio of the average particle diameters of the third active material particles to the average particle diameters of the fourth active material particles is (2.2-2.6):1; and / or, the average particle sizes of the first active material particles and the third active material particles are independently 0.4 μm to 0.8 μm; And / or, the average particle diameters of the second active material particles and the fourth active material particles are independently 0.15 μm to 0.4 μm.
6. The electrode sheet according to claim 1, characterized in that: The number of the second active material particles accounts for 1% to 60% of the total number of the first active material particles and the second active material particles in the first electrode material layer; And / or, the number of the fourth active material particles accounts for 1% to 60% of the total number of the third active material particles and the fourth active material particles in the second electrode material layer.
7. The electrode sheet according to claim 1, characterized in that: Along the length direction of the current collector, the width of the second active material particle region is greater than the width of the fourth active material particle region; and / or, along the length direction of the current collector, the widths of the first active material particle region and the third active material particle region are each independently 10 μm to 100 μm; And / or, along the length direction of the current collector, the widths of the second active material particle region and the fourth active material particle region are each independently 1 μm to 20 μm.
8. The electrode sheet according to claim 1, characterized in that: The maximum powder compaction density of the first active material particles and the third active material particles is independently 2.4 g / cm 3 ~2.8g / cm 3 ; and / or the maximum powder compaction density of the second active material particles and the fourth active material particles is independently 2.1 g / cm 3 ~2.5g / cm 3 ; And / or, the compaction density of the electrode sheet is 2.5 g / cm 3 ~2.7g / cm 3 .
9. The electrode sheet according to claim 1, characterized in that: The first active material particles, the second active material particles, the third active material particles and the fourth active material particles are selected from positive electrode active materials, and the positive electrode active materials include one or more of lithium transition metal oxides, lithium-containing phosphates, sodium transition metal oxides and sodium-containing phosphates; Alternatively, the first active material particles, the second active material particles, the third active material particles and the fourth active material particles are selected from one or more of lithium iron phosphate, nickel cobalt lithium manganese oxide ternary material, nickel cobalt aluminum oxide ternary material, lithium manganese oxide and lithium cobalt oxide.
10. The electrode sheet according to claim 1, characterized in that: The first active material particles, the second active material particles, the third active material particles and the fourth active material particles are selected from negative electrode active materials, and the negative electrode active materials include one or more of graphite, silicon and lithium titanate.
11. The electrode sheet according to claim 1, characterized in that: The thickness of the first electrode material layer and the second electrode material layer are each independently 80 μm to 120 μm.
12. A method for preparing the electrode sheet according to any one of claims 1 to 11, characterized in that: include: On at least one side of a current collector, alternately applying a first slurry and a second slurry along a length direction of the current collector to form a first electrode material layer including at least one region of the first active material particles and at least one region of the second active material particles, wherein the first slurry contains first active material particles and the second slurry contains second active material particles; On the side of the first electrode material layer away from the current collector, the third slurry and the fourth slurry are alternately applied along the length direction of the current collector to form a second electrode material layer including at least one third active material particle area and at least one fourth active material particle area, the third slurry contains third active material particles, and the fourth slurry contains fourth active material particles.
13. An electrochemical device, characterized in that: The electrode sheet comprises the electrode sheet according to any one of claims 1 to 11.
14. An electrical device, characterized in that: An electrochemical device comprising the electrochemical device of claim 13.
Citation Information
Patent Citations
Positive plate, preparation method thereof and battery
CN115692604A
Positive electrode for secondary batteries, and secondary battery
WO2024095667A1
Cited By
Energy storage device, vehicle, control method and electric energy transfer system
CN120895747A